Structural Performance of Circular Hollow Steel Damper with Fins and Gaps - Aritonang, Tobok S. M.; Satyarno, Iman; Awaludin, Ali; Setiawan, Angga F. (Civil Engineering Journal, 2026)
Prior studies have shown that fin reinforcement on a circular hollow steel damper (CHSD) could mitigate buckling and enhance shear strength. However, in bridge applications, repeated vibrations from lateral traffic loads and low-frequency cyclic actions may cause premature energy dissipation and fatigue damage, thus reducing the seismic performance of CHSD during design-level earthquakes. To address this issue, this study integrates fins and gaps into CHSD to enhance stability against buckling and to mitigate fatigue-induced damage. The CHSD specimens were fabricated in three variations: without fins, with fins, and with fins and gaps. Cyclic loading tests and nonlinear finite element analyses were conducted to evaluate their effects on mechanical properties and seismic performance. Cyclic loading was performed in accordance with the AISC 341-22 protocol and applied at 0° and 30° to simulate multidirectional lateral forces. The cyclic test results reveal that the addition of fins exhibits both beneficial and adverse effects on the mechanical properties and seismic performance of CHSD, while the gap reduces the equivalent viscous damping ratio. The backbone curves derived from the numerical analyses agree well with experimental results. Furthermore, the damper shear resistance and deformation capacity are delayed by the presence of gaps, mitigating fatigue-related damage.